ANALISIS RESPON PELAKU USAHA MINUMAN KOPI (COFFEE SHOP) TERHADAP KEWAJIBAN SERTIFIKASI HALAL - Ahmad, brilliant; Khoirul Anwar, Moch (Jurnal Ekonomika dan Bisnis Islam, 2020)
The government ratified the JPH Law, which took effect in October 2019. The law emphasizes that products circulating, imported, and sold in Indonesia must be halal certified. The various types of coffee drinks are very diverse and most of the products in circulation have not received halal certificates because the awareness of halal-certified products by business actors is still very low. The purpose of this study was to determine the response of coffee shop entrepreneurs regarding halal certification obligations that have been in force in Indonesia given the low awareness of business operators towards halal products. This research can be used as a solution in dealing with problems regarding halal certification obligations. The research method used by researchers is descriptive qualitative, namely through data that has been obtained and collected. The conclusion of this study shows that the responses issued by business actors strongly support the existence of the halal certification obligation, but there are problems in the implementation of the JPH Law making business actors still reluctant to conduct halal certification.